Metaverse and Banking Industry – 2023 The Year of Metaverse Adoption - Dubey, Vivek; Mokashi, Azher; Pradhan, Ranjan; Gupta, Paresh; Walimbe, Rohit (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
This whitepaper discusses the potential of Metaverse to revolutionize the banking industry. It highlights the various ways in which banks can leverage Metaverse to improve their operations, including through the use of NFTs, blockchain technology, and smart contracts. The paper is aimed to explore the possibilities of Metaverse in the Banking Industry and understand its practical implementation radius. This paper navigates to various topics from the definition of Metaverse to business aspects in banking and financial services. Explores the various business opportunities in the customer communication domain, cross-border transactions, mortgages, digital assets, green loans, and achieving carbon net zero through Metaverse. The role of Innovation Leaders is discussed in detail assisting readers to understand and appreciate the value of innovation in today’s rapidly changing technology times. The paper argues that banks must take a proactive role in driving the adoption of Metaverse, support circular economy, and reduce waste by enabling web3.0 technology in the banking sector.